Gis- Based Environmental Modeling for Integration of Urban Accessibility and Air Quality - Dahshal, Mehrdad Hadipour (2008)
Good establishment of urban transportation network in proportion to residential zones is an important element in urban planning. Increasing urban network has both positive (accessibility) and negative (air pollution) impacts. Accessibility and air quality are chosen as key elements with respect to their critical roles in quality of life and environmental impacts. A spatial and mathematical model is useful to find the effective functions and activities on accessibility and air quality. Also, it has capability to assign quantitative values to these functions. The overall objective of this study is to develop a decision support tool to plan appropriate locations for residential landuses and urban transportation network development through the use of spatial technologies to address two issues - accessibility and air quality. Methodology of this study helps to select suitable sites for development of urban transportation network and residential zones. Petaling Jaya, a developing city in Selangor, Malaysia has been chosen as a case study. This method can explain the linkage between accessibility and air quality. It covers the optimum accessibility from residential to commercial and administrative area along reducing air quality. There are two main focuses in this method: definition of the optimum distance between residential zones and roads based on mathematical model, and definition of the optimum location of residential zones in proportion to urban transportation network. In this method, calibration of a complex mathematical spatial decision support model for air pollution monitoring and quantitative interpretation of urban accessibility explores and arranges important criteria such as traffic volume, wind speed, and travel time which could be interpreted to predict suitable landuses and urban networks location in quantitative framework. The main finding of this research is a mathematical model, with about 90% accuracy, can be applied for the study area to find optimum distance from roads to avoid air pollution. Exploring potential locations for residential land use development as series of suitability maps to show current suitable and potential locations for future development is another finding of this research. Series of maps and quantitative parameters analyzed to find some area with good accessibility and air quality. The results show 66 % of study area has good accessibility and 20% of study area has potential for air pollution. The potential polluted areas are mostly located in residential landuse. Combination of accessible and non polluted areas with vacant lands and current residence areas show that 60% of current residential area are allocated in good accessible and air quality locations and with current transport network, 8% of study area has potential to develop for future. Also, there is a need to re-design of transportation networks and landuses for future development of residential zones. The spatial scenario planning framework developed in this research is an example of an effective integrated decision-making framework. This research has successfully managed to develop a scientifically based approach to convert conceptual configuration of non polluted and accessible areas into strategic locations using geospatial technology. Modeling for emitted air pollution by transportation, interpretation of transportation accessibility and analyzing the successful and non-successful current and future development has provided an efficient spatial approach for urban planning. It is hoped that this mathematical and spatial based approach can be employed in transportation planning and residential landuse suitability assessment at both the local and structure plan levels.